Dr. Neal Barnard's program for reversing diabetes : the scientifically proven system for reversing diabetes without drugs - Barnard, Neal D., 1953- (Rodale, 2017)
Outlines a nutritional approach to diabetes that claims greater efficacy and fewer complications than that of the American Diabetes Association diet, citing study participants who successfully improved their ability to respond to insulin.